Representation of Sufi Educational Values in the Dialogue "Feeling Smart, Even Being Stupid Doesn't Have It" by Rusdi Mathari - M Zainul Mukhtar; Siti Mutholingah; Rosidin Rosidin (Global Education Journal, 2026)
In the 21st century, the flow of globalization and technological advances have shaped people's lifestyles that tend to be hedonistic and materialistic. Relationships between people have become fragile and often detached from the foundation of religious values. This article aims to explain how Sufi values ​​are represented in the dialogue Feeling Smart, Stupid Even Though I Don't Have It by Rusdi Mathari to readers. This research uses a qualitative method with a library research approach. The data are in the form of sentences from the conversation between the character Cak Dlahom and his friends sourced from the book Feeling Smart, Stupid Even Though I Don't Have It. The results of the study show that the book contains Sufi values ​​presented through the daily life dialogues of Cak Dlahom and other characters, which include levels of remembrance of Allah, repentance, contentment, guarding oneself from arrogance, caring attitudes, solitude and silence, trust in God, sincerity, fighting lust, cleansing the heart, and piety. It can be concluded that the Sufi values ​​presented in the dialogue book Feeling Smart, Stupid, Not Having Any Benefits provide benefits, provide food for reflection, and enrich religious insight in everyday life, both at the individual and societal levels.